Changing Trends in Glaucoma Surgery Over the Past 5 Years in China. Issue 5 (28th May 2022) - Qiao, Chunyan; Zhang, Hui; Cao, Kai; Tian, Jiaxin; Chung, Tham Yih; Shan, Jing; Han, Ying; Wang, Ningli; ,
Abstract : Purpose: To analyze the trends of glaucoma surgery procedures over the past 5 years among hospitals across major provinces in China. Materials and Methods: This was a retrospective observational study based on medical records. We obtained the annual numbers of commonly performed glaucoma incisional surgeries from 57 hospitals of 30 provincial regions in the Chinese Glaucoma Study Consortium (CGSC) from January 2015 to September 2019. The trend of glaucoma surgery was analyzed by Cochrane-Armitage trend test. Results: Trabeculectomy, cataract extraction combined with goniosynechialysis, cataract extraction combined with trabeculectomy, and surgical peripheral iridotomy (SPI) were the top 4 surgical procedures percentages of which have the most substantial change over the course of 2015 to 2019 (all P trend <0.001). Numbers of trabeculectomies decreased significantly from 47.59% in 2015 to 31.21% in 2019; cataract extraction combined with goniosynechialysis increased from 12.12% to 28.48%; cataract extraction combined with trabeculectomy increased from 13.11% to 15.97%; and SPI decreased from 9.03% to 6.34%. The proportion of internal drainage surgery increased from 24.31% in 2015 to 39.29% in 2019 while external drainage surgery decreased from 69.20% to 54.64% (All P trend <0.001). The microinvasive glaucoma surgeries including AB-interno Canaloplasty, gonioscopy-assisted transluminal trabeculotomy, and Trabectome, increased from 0.62% to 1.40% ( P trend <0.001). Across all study hospitals, the trends were similar, except for the Tibet Autonomous Region Eye Center, where SPI and trabeculectomy remained the most common anti-glaucoma surgeries. Conclusion: In the past 5 years, we observed substantial reduction in trabeculectomy, and increase in combination cataract-glaucoma procedures across major hospitals in China. The proportion of internal drainage surgery increased, while external drainage surgery decreased significantly. Detailed understanding of shifting trends in glaucoma surgeries can facilitate better health care resource allocation and training of glaucoma subspecialists in China.